2013
DOI: 10.1098/rspb.2012.2238
|View full text |Cite
|
Sign up to set email alerts
|

Careful cachers and prying pilferers: Eurasian jays ( Garrulus glandarius ) limit auditory information available to competitors

Abstract: Food-storing corvids use many cache-protection and pilfering strategies. We tested whether Eurasian jays (Garrulus glandarius) reduce the transfer of auditory information to a competitor when caching and pilfering. We gave jays a noisy and a quiet substrate to cache in. Compared with when alone, birds cached less in the noisy substrate when with a conspecific that could hear but could not see them caching. By contrast, jays did not change the amount cached in the noisy substrate when they were with a competito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 23 publications
1
40
2
Order By: Relevance
“…The Eurasian jays tested were familiar with caching in similar seedling trays, and by using sand as the substrate, we prevented observers from hearing the caching events (Shaw and Clayton 2013). …”
Section: Methodsmentioning
confidence: 99%
“…The Eurasian jays tested were familiar with caching in similar seedling trays, and by using sand as the substrate, we prevented observers from hearing the caching events (Shaw and Clayton 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Previous experiments have indicated that Eurasian jays do attend to social context in caching and mate provisioning (Shaw & Clayton, 2012; Shaw & Clayton, 2013; Ostojić et al, 2013; Shaw & Clayton, 2014; Ostojić et al, 2014; Legg, Ostojić & Clayton, 2016). It is therefore still possible that jays use social information, but not for copying others’ choices, as none of the previous experiments required the birds to copy a demonstrator.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that socially housed Eurasian jays attend to social context to modify their caching and mate provisioning (courtship feeding) behaviour. For example, they prefer to cache in quiet rather than noisy substrates when in the presence of conspecifics that could hear but not see the subject (Shaw & Clayton, 2013); they attend to spatial and auditory cues when competitors are caching to later pilfer those caches (Shaw & Clayton, 2014); and subordinates inhibit caching in front of dominants and prefer to cache in less exposed areas (Shaw & Clayton, 2012). They also adjust their behaviour appropriately depending on whether they are caching or pilfering (Shaw & Clayton, 2014), and whether they compete with a dominant or subordinate (Shaw & Clayton, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Western scrub jays cache out of view or move their caches several times when conspecifics are present, presumably to reduce visual cues available to competitors (Dally et al, 2004; Dally et al, 2005). Eurasian jays ( Garrulus glandarius ) may even reduce acoustic information available to competitors by caching in quieter substrate (Shaw & Clayton, 2013), as other jays appear to use auditory information to locate and steal caches made by other jays (Shaw & Clayton, 2014). Scatter-hoarding tree squirrels also vary several behaviors in the presence of competitors: the amount of time and effort spent traveling to a cache site (Delgado et al, 2014; Hopewell, Leaver, & Lea, 2008; Leaver et al, 2007), the number of holes dug before selecting a final cache location (Delgado et al, 2014; Steele et al, 2008), and time spent covering a cache site with available substrate such as dirt or leaves (Delgado et al, 2014; Hopewell & Leaver, 2008).…”
Section: Introductionmentioning
confidence: 99%